Vol. 3, No. 1, September 2021 - FITRI DEWAN TINA (Scientia Regendi, 2021)
This research was carried out at the SAMSAT Joint Office of Central Bandung, Bandung City which was motivated by the fact that an interesting problem was the implementation of the service policy for the extension of vehicle number certificates that was not optimal. The purpose of this study was to determine, describe and analyze in depth the implementation of the policy for the renewal of vehicle registration certificates at the SAMSAT Office in Central Bandung. In analyzing the problem under study, the researcher uses George C Edward III's in Nugroho that is based on the factors theoretical approach, the factors of policy implementation consisting of communication, resources, attitude of implementers and bureaucratic structure. The method used in this research is descriptive method with a qualitative approach, as well as sources and data collection techniques using primary and secondary data sources collected through participant observation, in-depth interviews, and documentation. The data validity technique used is through triangulation. The results of this study indicate that the implementation of the STNK extension service policy will not be more optimal if the 4 main dimensions, communication, resources, disposition and bureaucratic structure are developed by adding one dimension, namely socialization, so the focus of this research will be optimal.